Microwave Reflection Based Dielectric Spectroscopy for Moisture Content in Melele Mango Fruit (Mangifera Indica L.) - Cheng, E.M.; A.B., Shahriman; Rahim @ Samsuddin, H.A.; Abdul Malek, M.F; Mohd Nasir, N.F.; Abdulaziz, N.; Abdul Majid, M.S.; Basaruddin, K.S. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The Melele mango is one of the special local fruit Malaysia and it has high commercial value. However, the current methods are not efficient in determining optimum period to harvest. The optimum harvest time has close relationship with moisture content in fruit. The reflection based dielectric spectroscopic technique is conducted to measure moisture in Melele mango fruits. Dielectric and reflection measurements were conducted over a frequency range from 200 MHz to 8 GHz on clone Melele mango. Dielectric constant, loss factor and complex reflection coefficient of Melele mango with different moisture content were measured using an Agilent E8362B PNA Network Analyzer in conjunction with an Agilent 85070E High Temperature Probe over a frequency range from 200 MHz to 8 GHz. The measured reflection coefficient is presented in magnitude and phase. Dielectric constant and loss factor decreases when the moisture content in mango fruit decreases. The magnitude of the reflection coefficient descends due to increment of the dielectric constant. The results show that the measured dielectric properties and complex reflection coefficient provides the ability to predict fruit moisture content.